USED OF PERSON DEIXIS IN MARIND LANGUAGE (A STUDY OF MARIND LANGUAGE IN MERAUKE PAPUA) - Marnina Marnina (Universitas Musamus, Merauke, Papua, 2017)
This study aims to describe the used deixis in Marind language. This research was done in Merauke. The population of the research was Marind people in Merauke, and the samples were 30 people selected by purposive sampling. The procedures of data were collected by using observation, interview, taking note and recording. The result of the analysis that in Marind language contains several types of deixis, including (1) personal deixis; (2) place deixis; (3) time deixis; (4) discourse deixis; and (5) social deixis. The Used of deixis in Marind language are determined by first singular person: Nok, Nok (object), Nahan and the first plural person: Yogh, Yahan, Yogha and third singular person: Eghel,/Eghul, Upe/Epe and Anupend/Anupendka.